Katalog Książki Śląskiej, czyli bibliografia dla niezaawansowanych (PDF 1,52 MB) (Książnica Śląska, 2025)
The text is a short presentation of the “Silesian Book”, a database created by the Municipal Public Library in Ruda Śląska. The LiteraryFest – Silesian Book Fair (its first edition took place in 2015 underthe name “Szolka Tyju” and is currently organized as “Kakauszale”),inspired the creation of this database. The “Silesian Book” includesvolumes published since 2015 and notes them in simplified descriptions.